Syntactic Structural Analysis of Print Media Language: the Case of Tell Magazine (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
This article investigates the syntactic structure of print media language, and demonstrates how standard the language is, if the language use follows the standard convention of writing or not, and it also looks at the clause structure of the sentences. Data used is obtained from Tell Magazine of August and November 2012, and it comprises of two issues which gives a total of one hundred and twenty-six (126) sentences. The result shows that most of the sentences used in Tell Magazine are complex; about 58.8% of them, 31.7% are simple sentences, 6.3% are compound sentences and 3.2% are compound - complex sentence. The investigation shows that complex sentences and independent clauses are used more than simple sentences and dependent clauses. However, complex nominal and verbal groups are frequently used more than the simple ones. Tell Magazine appears to have the upper middle class as its target audience. It is therefore the magazine could not be a good reader for secondary school students or people with poor English language background because very few of them may understand the style and discourse used in the magazine particularly its editorial columns.
Keywords: Syntax; Print Media; Analysis; Sentence Structure; Language